Performances of Some Perennial Grasses in Sustainable Energy Crops Cultivation - ÖZDOĞAN ÇAVDAR, Tuğçe; GEREN, Hakan (ISPEC Journal of Agricultural Sciences, 2023)
This study was conducted to bring out the effects of different harvest times on biomass yield and quality in giant king grass (Pennisetum hybridum), elephant grass (Miscanthus x giganteus) and switch grass (Panicum virgatum) plants, which are used extensively in sustainable energy crops cultivation in the world. The research was carried out in the experimental area of the Department of Field Crops, Faculty of Agriculture, Ege University between November 2019 and February 2021. Three different grass genotypes and two harvest dates (autumn and winter) were evaluated which was carried out in three replications according to the completely randomized block design. Some parameters were evaluated in the study such as number of tillers, plant height, stem diameter, biomass yield and ash content. While the highest biomass yield was obtained from the giant king grass plant harvested in autumn, the lowest ash content was obtained from the miscanthus plant harvested in winter.